Investigation of the structural, thermal, magnetic and cell viability properties of Ce/Sr co-doped hydroxyapatites - Ates, Hulya Gunes; Kaygili, Omer; Bulut, Niyazi; Osmanlioglu, Fatih; Keser, Serhat; Tatar, Beyhan; Ozcan, Imren (Elsevier, 2023)
The present study aims to give a more detailed report on the structural, thermal, magnetic and in vitro cell viability properties of the hydroxyapatites (HAps) co-doped with Sr and Ce at different amounts. Besides these experimental analyses, this study also includes the theoretical calculation results obtained from the modeled systems for the as-prepared samples. Diamagnetic behavior was observed for all the samples, as well as their high cell compatibilities. All the samples showed a thermally stable behavior, and the mass change mechanism and specific heat capacity were affected by the amount of the codopants. The bandgap value and linear absorption coefficient varied with the amount of both co-dopants. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Quantum mechanical calculations; Cell viability; Magnetic properties